Penerapan Metode Simple Additive Weighting (SAW) Dalam Pemilihan Oli Mesin Sepeda Motor Matic Terbaik di Bengkel Sepeda Motor - Marwah, Khoirul Wijak Alfaizh; Hasugian, Abdul Halim (Journal of Information System Research (JOSH), 2024)
The purpose of this research is to analyze and apply the Simple Additive Weighting (SAW) method in the context of determining motor oil brands, collect and process data on motor oil alternatives available on the market and evaluate the results of motor oil selection using the SAW method. This research identifies research variables adopted based on motorcycle engine oil criteria using the Simple Additive Weighting (SAW) method. There are four variables that form the basis of evaluation to determine the most popular shockbreaker brand: Size (C1), Type (C2), Viscosity (C3), Price (C4). The results of the study concluded that through the integration of the SAW method, researchers succeeded in building a comprehensive framework for evaluating relevant criteria in oil selection. The test results show that SAW is able to provide relative weights for each criterion used in this study and successfully rank oil alternatives based on the normalized value of each criterion. Based on the calculation results shown in the decision support system application, the first recommendation is Enduro Matic V followed by Yamalube Engine Oil Super Matic with a value of 1 and Shell Advance AX7 Scooter at rank 2 with a value of 0.96 and rank 3 AHM Oil Matic SPXX2 with a value of 0.863. The application that has been designed has a fairly good page display so that it provides convenience to users.